HIV/AIDS PREVENTION BEHAVIOR IN THE COMMUNITY OF MEN WHO HAVE SEX WITH MEN AND INFLUENCING FACTORS - Sugiarto Sugiarto; Pebriyaman Hanafi; Novi Berliana (Poltekkes Kemenkes Semarang, 2019)
HIV/AIDS has developed into a global health problem, including in Indonesia. The highest cumulative percentage of AIDS cases by way of transmission in Indonesia is through unprotected sex. Populations at high risk for HIV/AIDS transmission are gay (homosexual). This study aims to determine the description of HIV/AIDS prevention behavior and factors affecting the community of men who have sex with men. This study uses a cross-sectional design. The research sample was 79 male sex men in the city of Jambi. The sampling technique was purposive aside. Data were collected by interview using a questionnaire. Data were analyzed statistically using the chi-square test. Of the 79 respondents whose behavior of HIV/AIDS prevention was not good enough as many as 40 respondents (50.6%). 34 respondents (43.0%) had poor knowledge. Respondents whose attitudes were not good were 41 respondents (51.9%). 42 respondents (53.2%) had poor motivation. Statistical test results show that there is no relationship of knowledge with p-value= 0.177, and there is a relationship between attitude and p-value= 0.005 and there is a relationship of motivation with p-value= 0.000 HIV/AIDS prevention behavior in the community of men who have sex with men. The conclusion of the study is attitude and motivation are variables related to HIV/AIDS prevention behavior in the community of men who have sex with men.